Mesenchymal Stem Cells and Cutaneous Wound Healing: Current Evidence and Future Potential. (27th May 2015) - Isakson, M.; de Blacam, C.; Whelan, D.; McArdle, A.; Clover, A. J. P.
Abstract : Human skin is a remarkable organ that sustains insult and injury throughout life. The ability of skin to expeditiously repair wounds is paramount to survival. With an aging global population, coupled with a rise in the prevalence of conditions such as diabetes, chronic wounds represent a significant biomedical burden. Mesenchymal stem cells (MSC), a progenitor cell population of the mesoderm lineage, have been shown to be significant mediators in inflammatory environments. Preclinical studies of MSC in various animal wound healing models point towards a putative therapy. This review examines the body of evidence suggesting that MSC accelerate wound healing in both clinical and preclinical studies and also the possible mechanisms controlling its efficacy. The delivery of a cellular therapy to the masses presents many challenges from a safety, ethical, and regulatory point of view. Some of the issues surrounding the introduction of MSC as a medicinal product are also delineated in this review.